Kinetics of in-plane shear degradation in carbon/epoxy rods from exposure to alkaline and saline environments. (1st February 2017) - Tanks, Jonathon D.; Sharp, Stephen R.; Harris, Devin K.
Abstract: This paper investigates the degradation of in-plane shear properties in commercially-available carbon fiber/epoxy rods. Primarily, the intralaminar shear behavior of these rods was measured using the short-beam shear (SBS) test, in order to determine the degradation mechanisms affecting the matrix and fiber/matrix interface. A comparison is made after exposure to aqueous calcium-hydroxide (alkaline) and sodium-chloride (saline) conditions at temperatures of 20 and 60 °C for various durations. Additionally, the effect of confinement—provided by an exterior wrapping layer of synthetic yarn added during manufacturing—on intralaminar shear failure was determined. Microscopic examination of the failure surfaces shows that delamination occurs through fiber/matrix interfacial debonding, and some shear failure of the matrix in resin-rich areas. The moisture penetration from the aqueous solutions caused plasticization of the matrix, reducing the interfacial strength and resulting in deteriorated intralaminar shear strength (ILSS). Consequently, ILSS was relatively unaffected by confinement, but progressive delamination was subdued. A model is presented for predicting residual strength and characterizing degradation kinetics of in-plane shear properties.